Assessing Forest Resources in Mexico: Wall-to-Wall Land Use/Cover Mapping - Mas, J.-F.; Velázquez, A.; Palacio-Prieto, J.L.; Bocco, G.; Peralta, A.; Prado, J.
Mexico, encompassing a continental territory of nearly two millions square kilometers, is one of the five biologically richest countries, therefore considered as megadiverse. However, the country is undergoing rapid processes of land use /cover change with rates of deforestation of 0.25 and 0.76